ANALISIS KELAYAKAN FINANSIAL USAHA BUDI DAYA IKAN LELE DUMBO (Clarias gariepinus) DI KOLAM TERPAL DAN KOLAM PERMANEN PADA UD. REPUBLIK LELE KABUPATEN KEDIRI - Abidin, Zainal; Suryawan Wiranatha, A.A.P. Agung; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 2 (2019): Juni, 2019)
The purpose of the study was to analyze the financial feasibility of Clarias gareipinus cultivation in tarpaulin ponds and permanent ponds UD. Republik Lele in Kediri Regency, East Java. The method used is the analysis of profit-loss calculations using the Net Present Value (NPV), Internal Rate of Return (IRR), Net B / C Ratio, Pay Back Period (PBP), and Break Event Point (BEP). The results of the study show that. The results showed that the stages of catfish cultivation included the process of spawning, catfish egg hatching, seed grading, and the augmentation process. Spread density in permanent ponds of 500 seedlings / m2, tarpaulin ponds of 450 seedlings / m2 as a whole the business of profitable catfish cultivation, with an average net pool profit of Rp. 23,918,347 / cycle / pond and tarpaulin pool Rp. 19,005,054 / pool / cycle. Based on the analysis of financial feasibility of permanent ponds and tarpaulins in a row generate (NPV) Rp. Rp 5,975,446,295 and Rp 1,645,894,923 (IRR) of 17.62% and 10.57%, (PBP) for 3 years and 3 years 9 months, Net B / C Ratio of 1.20 and 1.19, and (BEP) in the amount of Rp. 11,082,314,678 and Rp. 8,238,792,702/year. This business is feasible to be developed. Keywords : financial feasibility, tarpaulin pool, permanent pond, catfish